Quae in ipso coitu observanda: técnica compositiva en un capítulo de la Universa muliebrium morbōrum medicīna de Rodrigo de Castro - González Manjarrés, Miguel Ángel (2021)
In this paper, we analyse Rodrigo de Castro's techniques of composition in a chapter taken from De universa muliebrium morb ō rum medic ī na (1.3.5). We seek to understand Castro's use of sources and examine his procedures for assembling his materials. Castro's technique is based on the reelaboration and relocation of data drawn from various sources (particularly the Gynaeci ō rum libri ), with the intent of providing a clear, well-ordered, manageable and useful text. A better knowledge of these compositional strategies will allow us to more justly appreciate the real contribution of this work on gynecology and obstetrics.
Neste texto analisa-se a técnica de composição de Rodrigo de Castro num capítulo do De universa muliebrium morbōrum medicīna (1.3.5). Pretende-se conhecer o modo como Castro maneja as suas fontes e que procedimentos utiliza para organizar os seus materiais. A técnica de Castro baseia-se na reelaboração e na realocação de dados retirados de várias fontes (especialmente dos Gynaeciōrum libri), com o objetivo de oferecer um texto claro, ordenado, manejável e útil. Conhecer este modo de composição permite avaliar melhor as reais contribuições deste trabalho em ginecologia e obstetrícia.
Keywords: Castro, Rodrigo de, -- 1546-1627; Estilística; Estética literaria